Edukasi Penggunaan Obat Selama Bulan Puasa di Puskesmas Rumbai Bukit - Firmansyah, Ferdy; Herliani, Noni; Jufanda, Yolla; Safitri, Yunita; Sri Agustini, Yustika; Zulfajri, Zulfajri (Universitas Pahlawan Tuanku Tambusai, 2023)
There are still considerable levels of drug use in several Indonesian regions. For health practitioners, like pharmacists in this case, raising public awareness about drug usage is still a task and struggle, particularly during the month of fasting. Meal timings will vary during Ramadan, thus it is necessary to modify the time you take your prescription as well. Medication that is taken every six or eight hours needs to be controlled in order for the patient to continue fasting. This project involved using pamphlets and surveys to educate 24 respondents about drug usage during the month-long fast at the Rumbai Bukit Community Health Center. The purpose of performing this community service is to perhaps educate the community on when to take medications during the fasting month, how to take medications correctly, and which medications do not interfere with fasting. Based on data analysis results, respondents who answered five questions correctly on the pre-test (i.e., with errors of 5, 4, 3, 2, and 1) had an average score of 0%, 4.16%, 50%, 41.6%, and 4.16% to 0% on the post-test, indicating an increase in public knowledge. In an attempt to educate or empower the community, it is advised that a planned and organized community service project be implemented.